Characterization of Methyl Ester Sulfonate (MES) from Mahagony (Swietenia macrophylla King) with Variations in H2SO4 Concentration and Sulfonation Duration - Laily Nurliana; La Ode Kadidae; Sunarti Sunarti; Rustam Musta (ALCHEMY Jurnal Penelitian Kimia, 2021)
Methyl ester sulfonate derived from mahogany (Swietenia macrophylla K.) oil has been characterized. The research began by synthesizing mahogany methyl ester (ME) in 4 stages: pressing, degumming, esterification, and transesterification. The next process was synthesizing methyl ester sulfonate (MES) also in four stages: sulfonation, bleaching, neutralization, and drying. The reactant for MES synthesis in this study was H2SO4 with a mole ratio of 1:6 and variations in the concentration of H2SO4 (70%, 75%, 80%, 85%, and 90%) as well as variations in the duration of sulfonation (45, 60, 75, 70, and 105 minutes) to determine the characteristics of the synthesized MES including density, acid number, and emulsion stability. The effect of the combination of treatment variations was analyzed using the two-way ANOVA test and the least significant difference (LSD) test. This research showed that MES from mahogany seed oil from a combination of variations in treatment has a density ranging from 0.91 to 0.97 g/mL where the LSD test at α = 0.05 produces three different MES density groups due to variations in the concentration of H2SO4 namely A (70 % and 75%), B (80% and 85%), and C (90%). The resulting MES acid numbers ranged from 4.69 ‒ 17.74 mgKOH/g sample with three different groups of MES acid numbers due to variations in the concentration of H2SO4, namely A (85 and 90%), B (75% and 80%), and C (70%). The stability of mahogany oil-based MES emulsion ranged from 0.000 ‒ 0.975 and two different MES emulsion stability groups were obtained due to variations in the concentration of H2SO4, namely A (80% and 85%) and B (70%, 75%, and 90%). FTIR spectrophotometer showed the presence of S=O groups at wavenumber 1172 cm-1 and S‒O groups at wavenumbers 972.12 cm-1 and 879.54 cm-1 proved that MES was successfully synthesized.